State-of-the-art of imaging detecting endoleaks post-EVAR with special focus on low-flow endoleaks. - Tengg-Kobligk, Hendrik von; Correa Londono, M.; von Allmen, Regula; Heverhagen, Johannes; Van den Berg, Josua Cornelis (The journal of cardiovascular surgery, 2014)
Endovascular aortic repair (EVAR) necessitates lifelong surveillance for the patient, in order to detect complications timely. Endoleaks (ELs) are among the most common complications of EVAR. Especially type II ELs can have a very unpredictable clinical course and this can range from spontaneous sealing to aortic rupture. Subgroups of this type of EL need to be identified in order to make a proper risk stratification. Aim of this review is to describe the existing imaging techniques, including their advantages and disadvantages in the context of post-EVAR surveillance with a particular emphasis on low-flow ELs. Low flow ELs cause pressurization of the aortic aneurysm sac with a low velocity filling, leading to difficulty of detection by routine imaging protocols for EVAR surveillance, e.g. bi- or triphasic multislice computed tomographic angiography, magnetic resonance imaging and contrast enhanced ultrasound. In this article, we review the imaging possibilities of ELs and discuss the different imaging strategies available for depicting low flow ELs
Gesehen am 16.07.2020